Upaya Gastrodiplomasi Indonesia Terhadap Cina - Sofie Zhafira; Kiky Rizky; Teguh Santosa (PRESIDENSI: Jurnal Politik dan Pemerintahan, 2025)
This research focuses on explaining how Indonesia's efforts to implement gastrodiplomacy towards China, especially through the Indonesia Spice Up The World program which took place in 2021-2024. Indonesia is a country rich in spices, so it has a diverse and rich cuisine. Although the relationship between Indonesia and China was once frozen, today the relationship between the two countries has developed and improved into a Comprehensive Strategic Partnership. China is known to be the first position country with the largest export value in Indonesia's export destination countries in the category of medicinal plants, aromatics, and spices in 2022. This research was conducted qualitatively with primary data collection techniques obtained through interviews with representatives from the Ministry of Tourism and Creative Economy and the Ministry of Foreign Affairs, as well as secondary data obtained through books, theses, journal articles, and news. This research uses the concepts of public diplomacy and gastrodiplomacy. This research found that Indonesia has made various gastrodiplomacy efforts including through the Indonesia Spice Up The World program conducted towards various countries including China. The program has not been able to achieve its targets due to various challenges and obstacles, especially in financing. In addition, until now the Indonesian government has not had a gastrodiplomacy program designed specifically for China alone.